2023
DOI: 10.5755/j01.erem.79.3.33084
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Stability of Biochar Obtained from 5 Species of Forest Biomass in Peru

Rosario Palacios-Hugo,
José Luis Calle-Maravi,
Mary Flor Césare-Coral
et al.

Abstract: The maintenance of the extensive parks at National Agrarian La Molina University (UNALM) generates a large amount of forest biomass, with high treatment costs. For this reason, the pyrolysis of the forest biomass is an alternative for valorization, allowing proper management producing biochar. The aim of the research was to evaluate the stability of biochar at 300°C and 500°C from forest biomass of five predominant species at UNALM, Grevillea robusta, Schinus molle, Casuarina cunninghamiana, Ficus benjamina an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The DBC feedstock contained a low ash composition (0.77%) compared with bamboo, which contained differences of 2.57% [46] and 8.69% in Ampel bamboo [72]. The difference in such chemical composition, even in bamboo feedstock, is caused by its structure, age, species, and part of the plant, affecting the composition of lignin, cellulose, hemicellulose, and other extractions [31,36,53].…”
Section: Table 1 the Results Of Proximate Analysis And The Elemental ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The DBC feedstock contained a low ash composition (0.77%) compared with bamboo, which contained differences of 2.57% [46] and 8.69% in Ampel bamboo [72]. The difference in such chemical composition, even in bamboo feedstock, is caused by its structure, age, species, and part of the plant, affecting the composition of lignin, cellulose, hemicellulose, and other extractions [31,36,53].…”
Section: Table 1 the Results Of Proximate Analysis And The Elemental ...mentioning
confidence: 99%
“…The results showed that the DBC had a high VM content (85.16%), a low MC (3.83%), and a low ash content (0.77%). All wood biomass typically has an acidic pH because all wood species are naturally acidic, caused by free acids and acidic groups, especially acetic acid and acetyl groups [31,36,55]. Therefore, the DBC feedstock was strongly acidic, with a pH of 5.07.…”
Section: Characteristics Of Dbc Feedstocksmentioning
confidence: 99%
See 1 more Smart Citation